The uncoupling of the inflammatory and structural components of airway hyperresponsiveness - Leigh, Richard (My University, 2004)
Airway hyperresponsiveness (AHR) is a characteristic feature of asthma. However, the mechanisms underlying AHR are complex and likely to be multi-factorial. A number of animal models have focused on understanding the mechanisms of transient airway inflammation and the associated transient airway dysfunction that occur following brief allergen exposure. While much has been learned about the role of acute inflammation in this brief allergen-induced response, a limitation of these studies is that the airway dysfunction is not fully representative of the AHR present in asthma. For example, we have shown that effective anti-inflammatory treatment results in only a modest reduction in AHR, indicating that AHR is usually sustained in asthma. This suggests that other mechanisms, including airway remodeling, likely play an important role in the pathophysiology of AHR. The subsequent focus of this thesis has been firstly, to demonstrate that sustained airway dysfunction develops in mice chronically exposed to allergen, and secondly, to explore the potential mechanisms and associations underlying this phenomenon. By subjecting sensitized mice to either brief or chronic periods of allergen exposure, we have developed a novel model in which chronic allergen exposure results in sustained airway dysfunction and structural changes of the airway. Subsequently, mice deficient for IL-4, IL-5 or IL-13 were studied using similar protocols. IL-4 and IL-13, but not IL-5, are critical for the development of airway remodeling, and in the absence of remodeling, mice were protected from developing sustained airway dysfunction. In further experiments, mice were either T cell immuno-depleted using monoclonal antibodies, or were treated with an anti-IL-13 fusion protein. When these interventions were given after chronic allergen exposure, at a time when airway remodeling was established, neither intervention attenuated the sustained airway dysfunction. Taken together, these results provide new information about basic physiological mechanisms underlying the sustained airway dysfunction present in asthma.
Keywords: physiology and pharmacology